Development of Covalent Ligand-Receptor Pairs to Study the Binding Properties of Nonpeptidic Neurotensin Receptor 1 Antagonists. - Kling, Ralf; Plomer, Manuel; Lang, Christopher; Banerjee, Ashutosh; Hübner, Harald; Gmeiner, Peter (ACS Chemical Biology, 2016)
The neurotensin receptor NTS1 has been suggested to be of pharmaceutical relevance, as it was found to exert modulatory effects on dopaminergic signal transduction and to be involved in tumor progression. Rational drug design of NTS1 receptor ligands requires molecular insights into the binding behavior of a particular lead compound. Although crystal structures of NTS1 have revealed the molecular determinants of peptide-agonist interactions, the binding mode of small-molecule antagonists remains largely unknown. Employing a disulfide-based tethering approach, we developed covalently binding molecular probes. The ligands 1 and 2 are based on the pharmacophore of the nonpeptidic NTS1 antagonist SR142948A, allowing the formation of a disulfide bond to an engineered cysteine residue of NTS1. The position of the covalent bond between Cys127(2.65) and the ligand was used to predict the binding mode of the covalent antagonist 1 and its parent compound SR142948A by molecular dynamics simulations.

Efficient synthesis of heterocyclic neurotensin receptor ligands by microwave-assisted aminocarbonylation - Lang, Christopher; Gmeiner, Peter (Synthesis-Stuttgart, 2013)
Marking the heterocyclic neurotensin receptor antagonist SR142948A as a lead compound, the development of an efficient and a practical synthetic route to heterocyclic aryl carboxamides is reported. Thus, a highly efficient and flexible access to these carboxamides was elaborated by taking advantage of microwave-assisted aminocarbonylation reaction mediated by Mo(CO), Herrmann's palladacycle, [(t-Bu)PH]BF, and DBU. © 2013 Georg Thieme Verlag Stuttgart New York.

Synthesis and evaluation of a 18F-labeled diarylpyrazole glycoconjugate for the imaging of NTS1-positive tumors - Lang, Christopher; Maschauer, Simone; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (Journal of Medicinal Chemistry, 2013)
Aiming to image NTS1 overexpressing tumors, the diarylpyrazole glycoconjugate 8, derived from the potent NTS1 antagonist SR142948A, was synthesized taking advantage of the palladium-catalyzed aminocarbonylation reaction. The glycoconjugate 8 displayed excellent affinity and selectivity toward NTS1. Radiosynthesis proceeded straightforwardly, obtaining [ F]8 with excellent stability and highly beneficial biodistribution in vivo as demonstrated by PET imaging in HT29 tumor-bearing nude mice. Thus, the tracer [F]8 represents a highly promising candidate for PET imaging of NTS1-positive tumors. © 2013 American Chemical Society.